Niacin intake and mortality (total and cardiovascular disease) in patients with cardiovascular disease: Insights from NHANES 2003–2018 - Ruiming Yang; Menghan Zhu; Shuzhen Fan; Jing Zhang (Nutrition Journal)
Abstract Background Cardiovascular disease (CVD) poses a significant challenge to global public health. Dietary intervention therapy offers high cost-effectiveness for treating CVD. Currently, there is limited research on the dietary niacin intake and survival of CVD patients. This study aims to examine the association of dietary niacin intake with long-term survival in people with CVD. Methods A nationally representative sample of 4,377 diabetes subjects was drawn from the NHANES (National Health and Nutrition Examination Survey) data collected between 2003 and 2018. Dietary niacin intake in this study represents either the average of the two recalls or the value from one recall (if only one recall was available for a participant). Weighted Cox proportional hazards regression models were used to calculate hazard ratios (HRs) and 95% CIs to examine the associations between dietary niacin intake and the risk of all-cause and CVD mortality. Results After adjustment for multiple covariates, HRs and 95% CIs in model 3 indicated that participants in the highest quartile (Quartile 4) of dietary niacin intake were at lower risk for all-cause mortality (HR = 0.74, 95% CI: 0.60–0.90, P for trend = 0.010) and CVD mortality (HR = 0.67, 95% CI:0.51–0.89, P for trend = 0.020). Conclusion Higher dietary niacin intake may be associated with a reduced risk of all-cause and cardiovascular disease mortality among CVD patients. Additionally, significant interactions were found between dietary niacin intake and BMI as well as vitamin B12 subgroups.